2023
DOI: 10.3389/feduc.2023.1174751
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on social justice when becoming a teacher-researcher in the practicum: insights from physical education teacher education

Luiz Sanches Neto,
Luciana Venâncio,
Luciano Nascimento Corsino
et al.

Abstract: Understanding the role teachers must play in fostering social justice is one of many tasks student teachers learn on practicum. This self-study is a collaborative endeavour between eight Brazilian teacher-researchers who work in multiple teaching positions and settings in different regions of the country. Our assumption within the broader research scope is that being a teacher-researcher has commonalities related to social justice whether teaching in K-12 schools or higher education. We have reconfigured a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For Filgueiras et al (2023), the concern with the social justice theme grew in Brazil from the progressive and critical conceptual framework of physical education in schools over the last 40 years. Although some studies have shown that this discussion takes place in schools, we still know little about how critical perspectives have impacted academic research and the practices and activism of teachers who build physical education in schools (Sanches Neto et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For Filgueiras et al (2023), the concern with the social justice theme grew in Brazil from the progressive and critical conceptual framework of physical education in schools over the last 40 years. Although some studies have shown that this discussion takes place in schools, we still know little about how critical perspectives have impacted academic research and the practices and activism of teachers who build physical education in schools (Sanches Neto et al, 2023).…”
Section: Introductionmentioning
confidence: 99%